The Oxford Encyclopedia of Curriculum Studies - Schubert, William Henry; He, Ming Fang (New York: Oxford University Press, 2022)
"The Oxford Encyclopedia of Curriculum Studies (OECS) addresses the central question of Curriculum Studies as: What is worthwhile? The articles show how the public, personal and educational concerns about composing lives are the essence of curriculum. Writ large, Curriculum Studies pertains to what human beings should know, need, experience, do, be, become, overcome, contribute, share, wonder, imagine, invent, and improve. While the OECS treats curriculum as definitely central to schooling, it also shows how curriculum scholars also work on myriad other institutionalized and non-institutionalized dimensions of life that shape the ways humans learn to perceive, conceptualize, and act in the world. Thus, while OECS treats perennial curriculum categories (e.g., curriculum theory, history, purposes, development, design, enactment, evaluation), it does so through a critical eye that provides counter-narratives to neoliberal, colonial, and imperial forces that have too often dominated curriculum thought, policy, and practice"--
Volume 1. A-D --
Includes bibliographical references and index.
Keywords: Curriculum Planning -- Encyclopedias; Curriculum change -- Encyclopedias; Education -- Curricula -- Encyclopedias; Curriculum change; Curriculum planning; Education -- Curricula; Encyclopedias; Handbooks and manuals